Radical possibilities : public policy, urban education, and a new social movement - Anyon, Jean (Critical social thought., 2005)
Jean Anyon's groundbreaking new book reveals the influence of federal and metropolitan policies and practices on the poverty that plagues schools and communities in American cities and segregated, low-income suburbs. Public policies ... such as those regulating the minimum wage, job availability, tax rates, federal transit, and affordable housing ... all create conditions in urban areas that no education policy as currently conceived can transcend. In this first book since her best-selling Ghetto Schooling, Jean Anyon argues that we must replace these federal and metro-area policies with.